Current concepts in diagnosis and treatment of chronic lymphocytic leukemia - Hus, Iwona; Roliński, Jacek (Contemporary Oncology/Współczesna Onkologia, 2015)
Chronic lymphocytic leukemia (CLL) is the most commonly diagnosed type of leukemia in Western Europe and North America, and represents about 30% of all leukemias in adults. Chronic lymphocytic leukemia is a disease of the elderly, who are often in poorer general health and burdened with multiple comorbidities. These factors affect the decision making when choosing an appropriate method of treatment. In recent years there has been significant progress in the treatment of chronic lymphocytic leukemia, first due to the introduction of immunochemotherapy with monoclonal antibodies and latterly small molecules, like tyrosine kinase inhibitors targeting B-cell receptor signaling. This article discusses the current diagnostic principles, the most important prognostic factors and therapeutic options, available in first-line treatment and in refractory/resistant disease, including high-risk CLL, both for patients with good and those with poor performance status. It also presents important novel molecules which have been evaluated in clinical trials.